Imported Zika Virus in a European City: How to Prevent Local Transmission? - Millet, Joan-Pau; Montalvo, Tomàs; Bueno-Marí, Ruben; Romero-Tamarit, Arancha; Prats-Uribe, Albert; Fernández, Lidia; Camprubí, Esteve; del Baño, Lucía; Peracho, Victor; Figuerola, Jordi; Sulleiro, Elena; Martínez, Miguel J.; et al. (Frontiers in Microbiology, 2017)
Background: On February 1st 2016 the WHO declared the Zika Virus (ZIKV) infection a worldwide public health emergency because of its rapid expansion and severe complications, such as Guillain-Barré Syndrome or microcephaly in newborn. The huge amount of people traveling to endemic areas and the presence of Aedes albopictus in Barcelona increase the risk of autochtonous transmission. The objective of this study was to describe the first ZIKV cases diagnosed in our city and to analyze the surveillance, prevention and control measures implemented to avoid autochthonous transmission. Methods: An observational cross-sectional population-based study in Barcelona, Spain was performed. An analysis of the socio-demographic, epidemiological, clinical characteristics and mosquito control activities of the ZIKV cases detected between January 1st and December 2016 was carried out using a specific ZIKV epidemiological survey of the Barcelona Public Health Agency. Results: A total of 118 notifications of possible ZIKV infections were received, and 44 corresponded to confirmed cases in Barcelona residents. Amongst these, the median age was 35 years and 57% were women. All cases were imported, 48% were Spanish-born and 52% foreign-born. Dominican Republic was the most visited country amongst foreign-born patients and Nicaragua amongst Spanish-born. The most frequent symptoms were exanthema, fever and arthralgia. Among the 24 diagnosed women, 6 (25%) were pregnant and there was one case of microcephaly. Entomological inspections were done at the homes of 19 cases (43.2% of the total) and in 34 (77.3%) public spaces. Vector activity was found in one case of the 44 confirmed cases, and 134 surveillance and vector control were carried out associated to imported ZIKV cases. In all cases prevention measures were recommended to avoid mosquito bites on infected cases. Conclusion: Epidemiological and entomological surveillance are essential for the prevention of autochthonous transmission of arbovirosis that may have a great impact on Public Health. The good coordination between epidemiologists, entomologists, microbiologists and clinicians is a priority in a touristic city with an intense relationship with endemic countries to minimize the risk of local transmission by competent vectors.